Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-58 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Sclerotomes (B) and Dermatomes (A).